2012
DOI: 10.1088/0143-0807/33/3/473
|View full text |Cite
|
Sign up to set email alerts
|

Variation in angular velocity and angular acceleration of a particle in rectilinear motion

Abstract: We discuss the angular velocity () and angular acceleration () associated with a particle in rectilinear motion with constant acceleration. The discussion was motivated by an observation that students and even teachers have difficulty in ascribing rotational motion concepts to a particle when the trajectory is a straight line. We present some details of our observations. A formal derivation of ω and α is presented which reveals ‘surprising’ and non-intuitive aspects, namely non-monotonic behaviour with an asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…The pedagogical significance of a proper treatment of the single particle case, to ensure a smooth transition to the many-particle system or rigid body, is scarcely appreciated. Recently, we observed that students and teachers have difficulty in ascribing rotational motion concepts to a particle in rectilinear motion (origin not on the path) [8]. We find that they have difficulties in comprehending ω and α of a particle in a variety of contexts.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The pedagogical significance of a proper treatment of the single particle case, to ensure a smooth transition to the many-particle system or rigid body, is scarcely appreciated. Recently, we observed that students and teachers have difficulty in ascribing rotational motion concepts to a particle in rectilinear motion (origin not on the path) [8]. We find that they have difficulties in comprehending ω and α of a particle in a variety of contexts.…”
Section: Introductionmentioning
confidence: 71%
“…Rotational kinematics of a particle is often given short shrift by text books [8]. After a brief discussion of ω and α in the context of uniform circular motion, the concepts are directly introduced for rigid bodies.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported this earlier as well. Plausible causes include lack of meaningful teacher-training programs, unimaginative evaluation systems, and other socioeconomic issues [30]. Moreover, science education research has, in general, not yet percolated to the Indian educational system, and thus has had limited impact.…”
Section: Discussionmentioning
confidence: 99%
“…components, the relation between angular acceleration and centripetal acceleration, and the relation between angular acceleration and tangential acceleration) (Mashood & Singh, 2012a, 2012b, iii) the rotational kinematics of a rigid body revolving around a fixed axis (thirteen items created to test torque, moment of inertia, rotational energy, and rolling-motion concepts) (Mashood & Singh, 2013). Rimoldini and Singh (2005) created a 30-itemized CI, in order to examine students' comprehension of rotational and the rolling-motion concepts in physics and to evaluate the efficacy of instructional methods to enhance students' understanding.…”
Section: Scope Of the Initial Scholarly Review -The Methodological Steps In Developing A CImentioning
confidence: 99%